Avaliação da evolução da resistência à compressão de alvenaria estrutural com blocos cerâmicos em idades iniciais - Barreto, José Maurício Lima (2015)
This paper presents an experimental study in order to assess the evolution of the compressive strength of structural masonry along the healing ages, through the prisms resistance study consisting of two structural ceramic blocks. There were compressive strength tests and modulus of elasticity of a type of the mortar, a trace of grout and no prisms grauteados and grauteados, in ages of 3, 7, 14 and 28 days. It was evaluated also in ages of 3, 7, 14 and 28 days, the evolution of the mortar resistance, depending on the molding method and the shape of the specimens. The structural ceramic hollow block wall was evaluated with respect to the geometric, physical, and mechanical characteristics. From the analysis of the test results, it was found that such structural ceramic block met the regulatory requirements. As to the compressive strength of mortar industrialized, it was found that the prismatic specimens exhibited compressive strength slightly higher when compared to the strength of cubic specimens. The compressive strength of the prisms, and not grauteados grauteados, showed high resistance to compression at 7 days of age.